Performance Modeling And Size Optimization Of A Standalone Photovoltaic System - Abdul Qayoom, Jakhrani (Universiti Malaysia Sarawak (UNIMAS), 2013)
Standalone photovoltaic (SAPV) systems are emerging source of generating electrical power especially for isolated villages. The remote villages, which cut-off from the national grid and where extension of power transmission lines is expensive due to their geographical conditions. Poor modelling algorithms, high initial capital cost and threat of system breakdown due to improper sizing of SAPV systems impede its growth. The available models were mostly validated by applying the long term (more than twenty years) solar radiation data with small time intervals from developed countries. The procedure for determination of input parameters required for the models was not well explained. The available intuitive sizing methods were found to be imperfect and the numerical methods were complicated and time consuming. Therefore, the development of an appropriate sizing method was necessary which should fill up the gap between complex and imprecise SAPV sizing methods.The aim of this work was to improve the prediction of SAPV system performance by proposing an appropriate sizing method. The original contribution of this work was the development of two mathematical models namely a model for determination of global solar radiation and a model for the estimation of PV module power output. Furthermore, a novel analytical size optimization method was formulated involving load demand on the basis of power reliability and system cost. The adapted global radiation model is different from available models as it incorporates the site specific and environmnetal parameters, which considered as influential input variables. It was found from the study that the adapted global solar radiation model performed well and displayed less than 10% RMSE and 8% MBE as compared to the examined models. The power outputs of PV modules were estimated by development of a single diode equivalent electrical circuit model. The values of input parameters for developed model were computed analytically. The expression for output current from PV module was determined explicitly by Lambert W function and the voltage output was computed numerically by Newton-Raphson method. The developed model executed ± 2% error with the rated power output of a PV module provided by the manufacturers. Furthermore, SAPV components sizing method was formulated with a nonlinear unconstrained optimization technique by using first derivative method. The proposed optimal sizing method determines the required PV array area and battery storage capacity for the system load with least possible cost and predefined power reliability.The results of the adopted models and developed sizing method were validated by conducting sensitivity analysis of model parameters. It was revealed that the most important and sensitive input variable was the total solar radiation with 2.5 times influence over the output results with a sensitivity index of 0.8. The lowest sensitive variable was wind speed with a sensitivity index of less than 0.1. The carbon footprints from diesel generators were estimated and compared with SAPV system emissions for environmental analysis. It is because the diesel generators are most common power producing units in remote areas of Sarawak. The analysis reveals that the power generated by SAPV systems will help to avoid 111 tonnes of CO2 to the atmosphere as compared to a 5kW rated power diesel generator with a load demand of 6.3kW/day. However, the estimated net energy cost occurred from SAPV system was found to be 20 times higher than average electricity tariff in Malaysia. It was found from the study that proposed sizing method is precise and easy to implement than previously available methods. It requires average solar radiation data, which is almost available in every place. It gives a complete procedure for determination of required model parameters and incorporates the load demand besides system cost and power reliability. It is concluded that the proposed optimal sizing method can be successfully implemented for the design, development, size optimization and feasibility study of SAPV systems for the supply of reliable power in isolated villages.